The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/1467-6427.12124
|View full text |Cite
|
Sign up to set email alerts
|

Couples’ depression and relationship satisfaction: examining the moderating effects of demand/withdraw communication patterns

Abstract: This study used systemic perspectives and actor and partner interdependence model to examine actor and partner effects of depression on couples’ relationship satisfaction in sixty‐three clinical couples. We also examined if a demand/withdraw communication pattern served a unique communication context that modified the impacts of depression on relationship satisfaction. Couples participated in a treatment‐as‐usual situation. The results showed that male depression had a negative impact on female relationship sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 46 publications
(61 reference statements)
3
23
0
3
Order By: Relevance
“…Using the APIM approach, as was expected according to systems theory (Becvar & Becvar, 1998) and the family systems-illness model (Rolland, 1994), our findings show a medium-strength correlation between the two members of the couple's depression levels. This result is consistent with previous studies that have reported an association between the two partners a couple depressive symptoms (Li & Johnson, 2018;Proulx et al, 2009). These correlations can be explained by direct effects such as the transmission of negative moods and by indirect effects through shared variances of depression-related couple outcomes (Gabriel et al, 2016;Proulx et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Using the APIM approach, as was expected according to systems theory (Becvar & Becvar, 1998) and the family systems-illness model (Rolland, 1994), our findings show a medium-strength correlation between the two members of the couple's depression levels. This result is consistent with previous studies that have reported an association between the two partners a couple depressive symptoms (Li & Johnson, 2018;Proulx et al, 2009). These correlations can be explained by direct effects such as the transmission of negative moods and by indirect effects through shared variances of depression-related couple outcomes (Gabriel et al, 2016;Proulx et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…However, our results suggest that in dual-earner couples men may be in a more vulnerable situation than their partners, considering that their overall life satisfaction may not only be affected by their own depression, but also by their partner's. Therefore, consistent with the suggestion made by Li and Johnson (2018), interventions to reduce depression in dual-earner couples should include both partners.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations